2005
DOI: 10.1089/jwh.2005.14.737
|View full text |Cite
|
Sign up to set email alerts
|

Stellate Ganglion Blockade Provides Relief from Menopausal Hot Flashes: A Case Report Series

Abstract: Successful SGB appears to be related to relief of hot flashes. Repeat SGB results in efficacious multiple week relief of severe hot flashes associated with menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…The trend seen in this present study, for hot flashes to become more prominent after an initial reduction, has been seen in previous studies done by Lipov et al In their reports, many of the patients received a second block 2–10 weeks after the first [19]. This use of two blocks led to reported benefit lasting for many months [16, 19, 20]. Therefore, it is possible that more than one stellate ganglion block would provide added benefit.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The trend seen in this present study, for hot flashes to become more prominent after an initial reduction, has been seen in previous studies done by Lipov et al In their reports, many of the patients received a second block 2–10 weeks after the first [19]. This use of two blocks led to reported benefit lasting for many months [16, 19, 20]. Therefore, it is possible that more than one stellate ganglion block would provide added benefit.…”
Section: Discussionsupporting
confidence: 87%
“…However, there are limited data on the use of stellate ganglion blocks to treat hot flashes, with the only known published manuscripts on this subject, to date, coming from Lipov et al; these investigators have reported a significant decrease in hot flashes in patients who undergo this therapy [16, 19]. In addition, a recent abstract from a different group of investigators reported similar benefits [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported our use of SGB to alleviate severe hot flashes (1). Based on evidence that the stellate ganglion has links with CNS nuclei that modulate body temperature-in particular, those of the insular cortex (2)-we proposed that E.G.…”
Section: To the Editormentioning
confidence: 99%
“…Potential treatments include hypnosis, 62 paced breathing/yoga and stellate ganglion block. 6366 Most of these have shown promise in pilot studies in women, but have not been studied in men with ADT-associated hot flashes. More information and evidence examining use of these methods of therapy will hopefully become available over the next several years.…”
Section: Other Non-pharmacological Treatmentsmentioning
confidence: 99%